Pengaruh Kecerdasan Emosional dan Lingkungan Kerja Terhadap Kinerja Pegawai pada Kantor Kecamatan Medan Kota - Sonya Prima Sari Girsang; Muhammad Alfahmi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The research analysis aims to find out whether emotional intelligence and the work environment have a positive and significant effect on employee performance at the Medan City District Office. The data analysis technique used is an associative research method with the help of the SPSS program. This research uses multiple linear regression analysis. The sample in this study was 43 respondents. Primary data collection uses a questionnaire. The research results show that emotional intelligence and the work environment have a positive and significant effect on employee performance at the Medan City District Office.